(untitled) (Práxis Educativa, 2022)
This article aims to address the concept of Afrocentric education, from the theory of Afrocentricity, disseminated mainly by the Afro-American educator and intellectual Molefi Asante, inserting some of its principles in the context of Latin American decolonial pedagogy, with special attention to the Brazilian educational context. The result of the approach points to the need to employ Afro-centered education and the Afro-centered curriculum as instruments for the realization of an authentic decolonial pedagogy. Keywords: Afro-centered education. Afrocentricity. Molefi Asante. Decolonial pedagogy. Brazilian education.